Stoechiométrie et écophysiologie d'une diatomée dominante en conditions arctiques - Schiffrine, Nicolas (Université Laval, 2020)
The Arctic Ocean is recognized as the most exposed and sensitive to climate change, as underscored by a drastic reduction in the extent of summer sea ice and rapid warming of the atmosphere and sea surface. By affecting the physico-chemical conditions of the water column (e. g. available light, temperature, nutrient inputs), these alterations can impact the global functioning and biogeochemistry of the marine ecosystem by triggering changes in the growth and elemental composition (stoichiometry) of phytoplankton at the base of the food web. Although, recent studies suggest that the carbon (C), nitrogen (N) and phosphorus (P) contents as well as the stoichiometry of polar phytoplankton differ from those of phytoplankton at lower latitudes, there is a lack of data assessing how the growth and elemental stoichiometry of ecologically-relevant diatoms respond to changing environmental conditions. Since the complexity of planktonic communities makes it difficult to study the physiological response of key species in situ, this thesis employs a parallel approach that experimentally probes into the influence of physical and nutritional conditions on the growth and stoichiometry of a cosmopolitan diatom in the laboratory. Chaetoceros gelidus is widely distributed in the Arctic Ocean and its ecological importance has been repeatedly emphasized. This unprecedented study of C. gelidus shows that at low temperatures, cell quotas and elemental stoichiometry are highly dependent on the initial nitrate:phosphate ratio in the culture medium. Beyond its obvious methodological implication, this result provides a basis for extrapolating knowledge gained in the laboratory to the natural Arctic environment, where ambient nitrate:phosphate ratios vary greatly from one sector to another. The work also demonstrates that C. gelidus is able to grow at appreciable and identical rates in the presence of different N forms with uneven energetic value, and is able to maintain a fixed stoichiometry regardless of the light level and nitrogen form ...